PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MATERI KERAGAMAN BUDAYA MELALUI MODEL BASIC LEARNING MENGGUNAKAN MEDIA WORDWALL KELAS V 4 METRO BARAT - wijayanto j, rahmat; Komang Febri Adi Dharma; Diah Ayu Kurniawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Maximum learning outcomes are a form of success in the learning process. In an effort to improve student learning outcomes in elementary schools, various methods are needed, one of which is by implementing learning methods and models. This study aims to determine the effectiveness of using the basic learning model assisted by worldwall learning media to improve learning outcomes in fifth-grade students at SD Negeri 3 Metro Barat in the Pancasila Education subject. The method used in this study is a type of Classroom Action Research (CAR) research conducted in two stages, where each stage consists of two meetings. In the pre-cycle stage, learning still uses the lecture method, resulting in low student activity and learning outcomes, with a completion rate of only 29.63%. In the first cycle, the application of the Basic Learning model and the use of wordwall began to show an increase in activity and learning outcomes, although classical completion only reached 44.44%. Improvements were then made in the second cycle by adding a variety of learning media, so that teachers can teach more effectively and students become more active. The results of the study show a clear increase in student participation and learning achievement in each cycle. Thus, the basic learning model with wordwall support has proven effective in improving student engagement and learning achievement on the topic of cultural diversity in Pancasila education